Dynamic decoupling analysis and experiment based on a class of modified Gough-Stewart parallel manipulators with line orthogonality. (January 2020) - Tong, Zhizhong; Gosselin, Clément; Jiang, Hongzhou
Abstract: In this paper, a class of modified Gough-Stewart parallel manipulators (MGSPMs) with line orthogonality is presented in order to fulfill the dynamic decoupling along the Z-axis. Relations between kinematic orthogonality, static orthogonality, and dynamic orthogonality are analytically formulated using double hyperboloids. Based on the derived formulas, it is proven that a class of MGSPMs with line orthogonality does exist, which expands the dynamic orthogonality from a point to a line. The evaluating factors are defined to carry out thorough cross coupling investigations. With the aid of numerical examples, a class of MGSPMs with line dynamic orthogonality is shown to exhibit large workspace with low coupling and high precision. A physical prototype is established and the experimental results confirm the high precision and approximately decoupled characteristics. The presented MGSPMs with line dynamic orthogonality possess better mechanical feasibility than conventional GSPMs. Moreover, two major constraints, namely that all six struts must have the same stiffness and a compliant center - which are difficult to satisfy - are removed or relaxed, thus greatly expanding the range of possible applications.